Technological quality of dough and breads from commercial algarroba-wheat flour blends - Correa, María Jimena (2017)
Algarroba flour is used to supplement lysinelimiting systems such as wheat flour due to its amino acidic composition. The effects of adding up to 30% of this flour to wheat flour (W-A30) on dough characteristics and breadmaking performance were studied. Dough rheology was tested by farinograph, oscillatory rheometry and texture profile analyses. Molecular mobility was evaluated by nuclear magnetic resonance, and thermal properties were analyzed by differential scanning calorimetry and viscoamylograph studies. Besides, different bread quality parameters were evaluated. Incorporation of algarroba flour resulted into increase in water absorption, development time and degree of softening, and decrease in stability of wheat flour, leading to softer, less adhesive and elastic dough, although at intermediate replacement levels cohesiveness improved. At the molecular level, a reduction of water activity and limited proton motion were observed in W-A30 samples, suggesting that protons were highly bound to the dough matrix. Dough samples with algarroba flour showed lower G0 and G00 values than the control, although with the formation of a more elastic structure for W-A30. In addition, algarroba flour produced a protective effect on starch granule disruption and interfered with amylose–amylose association during cooling. The specific volume of breads decreased with the increase in algarroba level, W-A30 reaching the highest decrease (15%). Bread crumbs with algarroba flour exhibited higher values of hardness and resilience. The use of algarroba flour resulted in lower quality when compared to the control. However, algarroba flour at 20% level can be added to wheat flour to obtain bakery products of similar technological quality and with improved nutritional components.